The Cyclin-Like Protein SPY1 Overrides Reprogramming Induced Senescence Through EZH2 Mediated H3K27me3. (17th September 2021) - Lubanska, Dorota; Qemo, Ingrid; Byrne, Megan; Matthews, Kaitlyn N.; Fifield, Bre-Anne; Brown, Jillian; Silva, Elizabeth Fidalgo; Porter, Lisa A.
Abstract: Fully differentiated cells can be reprogrammed through ectopic expression of key transcription factors to create induced pluripotent stem cells. These cells share many characteristics of normal embryonic stem cells and have great promise in disease modeling and regenerative medicine. The process of remodeling has its limitations, including a very low efficiency due to the upregulation of many antiproliferative genes, including cyclin dependent kinase inhibitors CDKN1A and CDKN2A, which serve to protect the cell by inducing apoptotic and senescent programs. Our data reveals a unique cell cycle mechanism enabling mouse fibroblasts to repress cyclin dependent kinase inhibitors through the activation of the epigenetic regulator EZH2 by a cyclin-like protein SPY1. This data reveals that the SPY1 protein is required for reprogramming to a pluripotent state and is capable of increasing reprogramming efficiency. : Reprogramming of normal fibroblasts to induced pluripotent stem cells is characterized by low efficiency due to the upregulation of tumor suppressors and reprogramming-induced senescence (RIS). Spy1 can be combined with classical pluripotency factors to override RIS through activation of EZH2 followed by an increase in trimethylation of histone H3 at the lysine 27 residue.